HUBUNGAN KADAR KARBOKSIHEMOGLOBIN DENGAN HEMATOKRIT DALAM DARAH MAHASISWA TINGKAT AKHIR TERPAPAR KARBONMONOKSIDA DI SEKOLAH TINGGI ILMU KESEHATAN NASIONAL - Wijanarko Wijanarko; Mastuti Widi Lestari (Journal of Indonesian Medical Laboratory and Science, 2022)
Carboxyhemoglobin is a substance formed due to the bonding of carbon monoxide with haemoglobin, which results in a lack of oxygen in the body, causing polycythemia which leads to an increase in blood hematocrit. motorized. This research method uses quantitative. The subjects of this study amounted to 30 people where the subjects were divided into 2 categories, namely smokers and motorcyclists. Data analysis using Shapiro Wilk and Rank Spearman Based on the research, it was found that the average COHb level was 6.06 while the average hematocrit in the normal range obtained p values ??> 0.05 for COHb 0.827, 0.836 and 0.827 while the hematocrit was 0.827, 0.836 and 0.827. This study concludes that there is no relationship between carboxyhemoglobin levels and hematocrit levels in final year students who are exposed to carbon monoxide from cigarette smoke and motor vehicle fumes.